Rancang Bangun Sistem Informasi Produksi Celana Berbasis Web Dengan Model Waterfall dan Pengujian Blackbox - Mira Permatasari; Nur Nawaningtyas Pusparini (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
Information Systems are a collection of systems in their aspects consisting of software, hardware and brainware in a structured manner with performance in a gradual and interconnected process so as to create a particular product that users need, especially the production of trousers in companies generally has processes such as production planning, production of goods, delivery of goods and goods reports, the aim of the research is to design an information system regarding the production of trousers for existing employees based on a website with a waterfall model in stages and testing using a black box on functional features, the final result is the creation of an information system for the production of trousers for production employees with website-based waterfall method